Factors associated with irritable bowel syndrome among medical students at Ain Shams University - Doaa Elhosseiny; Nehal Elfawy Mahmoud; Ayat F. Manzour (SpringerOpen, 2019)
Abstract Background Irritable bowel syndrome (IBS) is one of the most common and potentially disabling gastrointestinal disorders. The pathogenesis of this disorder remains obscure. However, many etiological explanations point toward bacterial etiology. Also, several studies have documented that psychological and social factors may play a role. Medical education is among the most challenging and stressful education, and this may predispose to high rates of IBS. Objectives The aims of this study are to estimate the frequency of IBS in a selected sample of students of Faculty of Medicine in Ain Shams University and to find out the determinants associated with this disorder. Study design A cross-sectional study was carried out among medical students from October 2017 to February 2018 at Faculty of Medicine-Ain Shams University. All participants were asked to complete a confidential self-administered questionnaire. An interview questionnaire was used for diagnosis of IBS according to Rome III criteria, while morbid anxiety and depression were diagnosed by using the Arabic version of Hospital Anxiety and Depression Scale (HADS). Results Three hundred eighty-two students completed the questionnaire. The frequency of IBS was 31.7% with higher proportion among females and among students with positive family history of IBS. However, IBS was significantly less prevalent among students practicing regular exercise. Lastly, based on (HADS), there was a statistical significant relationship between IBS and anxiety (p < 0.05), but not depression. Conclusion The study revealed that around 31% of the studied group was suffering from IBS. Female gender, suffering from anxiety, and positive family history of IBS were the main associated factors for IBS. Screening of all medical students in the faculty for IBS is suggested. Providing psychological and emotional support along with stress management is highly recommended.